Application of an experiment as a pedagogical resource to introduce astronomy teaching in the first grade of the basic teaching cycle (Research, Society and Development, 2023)
This work is a report on the application of an experiment to find a pedagogical resource that was both simple and playful, but capable of transmitting physical concepts behind astronomy to children who are starting the basic cycle of teaching astronomy. to promote their active participation. The work describes, in the form of a report, an activity in the classroom in which an experiment was carried out on the decomposition of white light and the role of a spectroscope for children in the first grade of primary cycle I. The experiment was built with elementary materials and low cost with the aim of allowing students to redo them on another occasion. The research developed in this activity sought to investigate how children behave when carrying out experimental activities in terms of participation, involvement, and motivation and to obtain data related to the previous knowledge they had about astronomy. Thus, the work brought elements to reflect the feasibility and importance of approaching physics knowledge in the initial series of the primary cycle. It was found that the level of learning was satisfactory and that the use of an experiment was an important aid tool for the teaching-learning process.